Key concepts in sociology - Braham, Peter (London : SAGE, 2013)
"Sociology consists of a myriad of frequently confusing concepts. Key Concepts in Sociology provides a comprehensive, lively and clearly-written guide to the most important concepts in the subject. It includes both what might be regarded as 'classic' sociological concepts, such as 'class', 'bureaucracy' and 'community', as well as subjects that have become increasingly prominent in recent times, such as 'celebrity', 'risk' and 'the body'."--pub. desc.
Alienation ; Anomie -- Bureaucracy -- Capitalism ; Celebrity ; Citizenship ; Class ; Community ; Consumption ; Culture -- Development ; Deviance ; Discourse ; Division of Labour -- Economic Sociology ; Equality ; Everyday Life -- Family ; Feminism -- Gender ; Globalization -- Identity ; Ideology -- Modernity and Postmodernity -- Orientalism -- Positivism ; Public Sociology -- Qualitative and Quantitative Research -- Race ; Rational Choice ; Risk -- Social Exclusion ; Social Justice ; Social Mobility ; Social Movements ; Social Stratification ; Society -- The Body.
Includes bibliographical references (pages 182-204) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sociology; Electronic books